2022
DOI: 10.3390/antiox11050865
|View full text |Cite
|
Sign up to set email alerts
|

Role of Iron in Aging Related Diseases

Abstract: Iron progressively accumulates with age and can be further exacerbated by dietary iron intake, genetic factors, and repeated blood transfusions. While iron plays a vital role in various physiological processes within the human body, its accumulation contributes to cellular aging in several species. In its free form, iron can initiate the formation of free radicals at a cellular level and contribute to systemic disorders. This is most evident in high iron conditions such as hereditary hemochromatosis, when accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…This itself is curious, as ferritin is primarily an intracellular protein, and the release into the circulatory system is itself an indicator of cellular disruption. Macrophages are tasked with the collection of poorly chelated iron, and the presence of iron-laden macrophages is another hallmark noted in individuals prone to neurodegenerative disease [ [113] , [114] , [115] ].…”
Section: Mechanistic Insights To Mitochondrial Dysfunction In Neurode...mentioning
confidence: 99%
“…This itself is curious, as ferritin is primarily an intracellular protein, and the release into the circulatory system is itself an indicator of cellular disruption. Macrophages are tasked with the collection of poorly chelated iron, and the presence of iron-laden macrophages is another hallmark noted in individuals prone to neurodegenerative disease [ [113] , [114] , [115] ].…”
Section: Mechanistic Insights To Mitochondrial Dysfunction In Neurode...mentioning
confidence: 99%
“…A high calorie, high protein diet with antioxidants such as vitamin C and vitamin E may help mitigate the damage done by iron overload. [18]…”
Section: Nutritional Strategiesmentioning
confidence: 99%
“…Experimental data have demonstrated that intracellular iron content increases during replicative and stress-induced senescence in normal cells [44,45]. Accordingly, iron accumulation in tissue has been associated with aging and with the development of age-related diseases [46,47]. Although alterations in proteins involved in iron metabolism have been reported in senescent cells, the role of iron in senescence has not been clarified.…”
Section: Iron In Cancer and Senescencementioning
confidence: 99%